2018
DOI: 10.1038/s41598-018-21321-0
|View full text |Cite|
|
Sign up to set email alerts
|

Proximity of breeding and foraging areas affects foraging effort of a crepuscular, insectivorous bird

Abstract: When complementary resources are required for an optimal life cycle, most animals need to move between different habitats. However, the level of connectivity between resources can vary and, hence, influence individuals’ behaviour. We show that landscape composition and configuration affect the connectivity between breeding (heathlands) and foraging habitats (extensively-grazed grasslands) of the European Nightjar (Caprimulgus europaeus), a crepuscular insectivorous bird. On a daily basis, nightjars connect bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 62 publications
6
58
0
Order By: Relevance
“…We observed a general increase in both moth richness and diversity with the advancement of the season, reaching the highest values during the nestling provisioning period (Alexander and Cresswell 1989;Cross et al 2005). While it is known that Nightjars can forage far away from the nesting site (up to 4km, Evens et al 2017), enhanced food availability in close proximity to the nesting site most likely reflects the optimal foraging habitat for food-provisioning parents (Evens et al 2018). A potential explanation for reduced prey abundance in aban-doned and restored Nightjar sites may result from the restoration management itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed a general increase in both moth richness and diversity with the advancement of the season, reaching the highest values during the nestling provisioning period (Alexander and Cresswell 1989;Cross et al 2005). While it is known that Nightjars can forage far away from the nesting site (up to 4km, Evens et al 2017), enhanced food availability in close proximity to the nesting site most likely reflects the optimal foraging habitat for food-provisioning parents (Evens et al 2018). A potential explanation for reduced prey abundance in aban-doned and restored Nightjar sites may result from the restoration management itself.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that Nightjars show a certain degree of plasticity in spatial foraging behaviour (Evens et al 2017, Sharps et al 2015. In order to reach optimal feeding grounds birds can travel long distances, which is however physiologically costly (Evens et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the overexpression of this protein is often associated with the development of multidrug resistant phenotype in cancer and disadvantageous clinical prognosis. 39 An emerging research approach is the use of efflux pump inhibitors as adjuvant compounds (so-called "chemosensitisers") to improve the efficacy of antitumour therapy, by co-administering them with chemotherapeutic agents. Computer-aided drug design techniques are used for the rapid assessment of chemical libraries in order to guide and speed up the early-stage development of new active compounds.…”
Section: Electrochemistry and Spectroelectrochemistrymentioning
confidence: 99%
“…Indeed, and for example, it has been demonstrated that in this species, the number of chicks fledged per nest was higher in close proximity to cereal crops, whilst it decreased gradually as the distance to the nearest cereal crop increased (Kafi et al 2015). Closer proximity to feeding areas would also increase the food acquisition efficiency in adult doves whilst allowing them to spend more time caring for their broods (Pearse et al 2004;Dunn et al 2010;Hanane 2015;Hanane 2018;Evens et al 2018). The maximum distance measured between the nest tree and the farthest turtle dove observed is relatively short (less than 1.6 km) and comes to support these explanations.…”
Section: Discussionmentioning
confidence: 88%